PENGARUH LAMA PENGUJIAN TERHADAP SERANGAN PENGGEREK KAYU DI LAUT PADA KAYU MALAPOGA (Toona ciliata) DAN KAYU TEA (Artocarpus elasticus Reinw. Ex Blume) - Fauziah Ramadhana; Abdul Hapid; Erniwati Erniwati (Universitas Andi Djemma Palopo, 2021)
Timber in brackish waters and at sea is often damaged by marine wood borer (marine borers). For some fishing communities and people living in coastal areas, the use of boats is very important for them as a support for their livelihood as a means of transportation. Until now, the use of wood as raw material for boats is still frequently used. The wood used in boat building will of course often come in contact with sea water so that it does not rule out the attack of marine borers that will reduce the strength of the wood especially if it is used for a long time. The research objective was to determine the effect of the length of testing at sea on the strength (MOE and MOR) and the natural durability of Malapoga wood (Toona ciliata) and Tea wood (Artocarpus elasticus Reinw. Ex Blume). This research was conducted for 3 months at the Material Testing Laboratory, Faculty of Engineering and Agrotechnology Laboratory, Faculty of Agriculture, Tadulako University, while testing for marine borers was carried out in the waters of Talise Village, East Palu District, Palu City, Central Sulawesi. The test uses the Malapoga wood and Tea wood test samples with sizes2 cm x 2 cm x 30 cm. Meanwhile, at sea testing and data analysis using a completely randomized design (CRD) factorial pattern with 2 factors was repeated 5 times so that there were 30 samples with 10 test samples (control) without immersion in the sea. The results showed that the length of the test had a very significant effect on the strength of wood (MOE and MOR) and the natural durability of wood (weight loss percentage) and the types of Malapoga wood and Tea wood were classified in the strong class V (five).